Electricity residential demand elasticities: Urban versus rural areas in Portugal. (1st February 2018) - Silva, Susana; Soares, Isabel; Pinho, Carlos
Abstract: We study the difference between urban and rural elasticities for electricity residential consumption in Portugal. Our sample covers the period from 1989 to 2010 and consists of five independent surveys. We adopt the pseudo-panel methodology creating 350 cohorts based on the size of the household, the type of location (rural or urban), the region, and the income quintile. Our results indicate that rural and urban populations have different behaviors. In particular, rural households are more sensitive to price changes than urban ones. This may happen because rural populations can more easily use other energy sources, for example, wood, for cooking and heating. As a consequence urban populations will be more affected by electricity price changes.